Bases para um programa de melhoramento florestal da espécie Quercus suber L. - Ribeiro, M M A (Revista Florestal, 1995)
The existing symptoms of degradation in cork oak stands requires the improvement on them, namely with plants that might produce cork in quantity and of good quality. It is urgent to develop an improvement program for this species spread in 664 thousand ha in our country (i. e. 1/3 of the whole area covered with cork oak in the world). Fifty five per cent of the world cork production comes from that area whose size could be extended more than 200 thousand ha. In the present work improvement programs for forestry species are brought into focus, and so are the different techniques of vegetative propagation, due to the importance they have in the development of these programs related either to the mass phenotypic selection (to estimate heritability and genetic gain) or to the clonal propagation of improved material. Maturative process in forest trees is questioned once it might condition the use of vegetative propagation and the techniques used to overcome that process are referred. Finally strategies for the improvement of cork oak, in the short and long term, are named.
Keywords: Cork oak; forest tree improvement; Quercus suber L.; vegetative propagation